Academy preparation - Collins, D.; MacNamara, A. (Talent development: A practitioner guide, 2018)
A successful talent development environment (TDE) should nurture young athletes effectively enabling them to realise their full potential. The aim of this chapter is to consider and provide evidence of effective TDEs. This information should then provide parents, coaches and athletes themselves with the evidence base to make informed decisions about quality when choosing academies or talent development environments. The importance of the individualised, often unpredictable pathway that young athletes take as they progress is explored against an understanding of key features of the TDE and how these should be operationalised to provide a player-centred approach to the realisation of potential. Based on mechanistic principles, this chapter will focus first on the long-term principles that should underpin a quality TDE and, second, describe the principles of an effective TDE, and how they are operationalised in practice.